Multi-year training load structure in the sprinter training system - Skrygin, S. V.; Yurchenko, A. L.; Zhigareva, O. G.; Sidorov, A. S. (International Journal of Applied Exercise Physiology, 2021)
The research addressed the task of building a multi-year training load structure for short-distance runners. In the course of the work, advanced practical experience was generalized, scientific and methodological literature was analyzed, and statistical data processing methods were used. The article hypothesized that the creation of a multi-year training system of sprinters based on the gradualness and succession principle is possible with the integrated use of results of scientific and experimental activities of the authors, who published their recommendations separately for beginners and qualified athletes. The integrated use of the data available in the scientific literature will make it possible to reduce the subjective influence and to designate an objective trend for more effective management of the multi-year training process for sprinters. The research work result is the multi-year training load structure for training the short-distance runners.